WNT inhibition creates a BRCA‐like state in Wnt‐addicted cancer. Issue 4 (4th March 2021) - Kaur, Amanpreet; Lim, Jun Yi Stanley; Sepramaniam, Sugunavathi; Patnaik, Siddhi; Harmston, Nathan; Lee, May Ann; Petretto, Enrico; Virshup, David M; Madan, Babita
Abstract: Wnt signaling maintains diverse adult stem cell compartments and is implicated in chemotherapy resistance in cancer. PORCN inhibitors that block Wnt secretion have proven effective in Wnt‐addicted preclinical cancer models and are in clinical trials. In a survey for potential combination therapies, we found that Wnt inhibition synergizes with the PARP inhibitor olaparib in Wnt‐addicted cancers. Mechanistically, we find that multiple genes in the homologous recombination and Fanconi anemia repair pathways, including BRCA1, FANCD2, and RAD51, are dependent on Wnt/β‐catenin signaling in Wnt‐high cancers, and treatment with a PORCN inhibitor creates a BRCA‐like state. This coherent regulation of DNA repair genes occurs in part via a Wnt/β‐catenin/MYBL2 axis. Importantly, this pathway also functions in intestinal crypts, where high expression of BRCA and Fanconi anemia genes is seen in intestinal stem cells, with further upregulation in Wnt‐high APC min mutant polyps. Our findings suggest a general paradigm that Wnt/β‐catenin signaling enhances DNA repair in stem cells and cancers to maintain genomic integrity. Conversely, interventions that block Wnt signaling may sensitize cancers to radiation and other DNA damaging agents. Synopsis: This study identifies that Wnt/β‐catenin signaling regulates homologous recombination and Fanconi anaemia DNA repair pathways in Wnt‐high cancers and intestinal stem cells. Wnt signaling inhibition induces a BRCA‐like state; and Wnt and PARP inhibitors synergize to inhibit Wnt‐addicted cancers. Wnt signaling regulates the expression of a broad set of genes involved in repairing DNA double‐strand breaks. This is mediated in part via the transcription factor MYBL2. Wnt inhibition creates a BRCA‐like state by inhibiting the expression of genes in the homologous recombination and Fanconi anemia DNA repair pathway. Wnt inhibition synergizes with PARP inhibitors to more effectively treat multiple Wnt‐addicted cancers. Wnt inhibition causes homologous recombination deficiency that, when combined with blockage of PARP‐mediated ssDNA repair leads to an accumulation of dsDNA breaks to enhance senescence. Wnt signaling also regulates Homologous recombination and Fanconi Anemia pathway genes in intestinal stem and transit amplifying cells. Abstract : This study identifies that Wnt/β‐catenin signaling regulates homologous recombination and Fanconi anaemia DNA repair pathways in Wnt‐high cancers and intestinal stem cells. Wnt signaling inhibition induces a BRCA‐like state; and Wnt and PARP inhibitors synergize to inhibit Wnt‐addicted cancers.